Management of security system in UiTM / Mohd Afiq Farhan Mohd Nor - Mohd Nor, Mohd Afiq Farhan (2007)
Nowadays the security system is a very important factor to consider especially to the higher institutional likes UiTM Shah Alam. As World Class University, an efficient management of security system is needed to ensure the proper and good performance of security system is applied. It also will help the security department to improve their quality of work and reduce number of risks or problems occur to campus in respect of security. The purpose of this research is to identify the various type of security component are used in higher institutional building and office building. It is also to study the management of security apply in UiTm Shah Alam and to identify the benefit from using the proper management of security system to the campus. All the information will be done by two methods. First, information will be getting through from the interview session between author and security department officer in UiTM Shah Alam. Second method is feedback from the disseminating questionnaire to the selective students.